Dynamics of Plasma Refill Rate and Intradialytic Hypotension During Hemodialysis: Retrospective Cohort Study With Causal Methodology. Issue 4 (14th April 2023) - Wang, Christina H.; Negoianu, Dan; Zhang, Hanjie; Casper, Sabrina; Hsu, Jesse Y.; Kotanko, Peter; Raimann, Jochen; Dember, Laura M.
Abstract : Abstract : Key Points: Directly studying plasma refill rate (PRR) during hemodialysis (HD) can offer insight into physiologic mechanisms that change throughout HD. PRR at the start and during HD is associated with intradialytic hypotension, independent of ultrafiltration rate. A rising PRR during HD may be an early indicator of compensatory mechanisms for impending circulatory instability. Background: Attaining the optimal balance between achieving adequate volume removal while preserving organ perfusion is a challenge for patients receiving maintenance hemodialysis (HD). Current strategies to guide ultrafiltration are inadequate. Methods: We developed an approach to calculate the plasma refill rate (PRR) throughout HD using hematocrit and ultrafiltration data in a retrospective cohort of patients receiving maintenance HD at 17 dialysis units from January 2017 to October 2019. We studied whether ( 1 ) PRR is associated with traditional risk factors for hemodynamic instability using logistic regression, ( 2 ) low starting PRR is associated with intradialytic hypotension (IDH) using Cox proportional hazard regression, and ( 3 ) time-varying PRR throughout HD is associated with hypotension using marginal structural modeling. Results: During 180, 319 HD sessions among 2554 patients, PRR had high within-patient and between-patient variability. Female sex and hypoalbuminemia were associated with low PRR at multiple time points during the first hour of HD. Low starting PRR has a higher hazard of IDH, whereas high starting PRR was protective (hazard ratio [HR], 1.26, 95% confidence interval [CI], 1.18 to 1.35 versus HR, 0.79, 95% CI, 0.73 to 0.85, respectively). However, when accounting for time-varying PRR and time-varying confounders, compared with a moderate PRR, while a consistently low PRR was associated with increased risk of hypotension (odds ratio [OR], 1.09, 95% CI, 1.02 to 1.16), a consistently high PRR had a stronger association with hypotension within the next 15 minutes (OR, 1.38, 95% CI, 1.30 to 1.45). Conclusions: We present a straightforward technique to quantify plasma refill that could easily integrate with devices that monitor hematocrit during HD. Our study highlights how examining patterns of plasma refill may enhance our understanding of circulatory changes during HD, an important step to understand how current technology might be used to improve hemodynamic instability.